Can Ethics Be Improved in the Banking System in Malaysia? An Exploratory Study of Banks in Klang Valley - Ramli, Mohd Sheridan (2013)
Of the recent financial crises, U.S. subprime crisis in 2008 is the most notable one, the members of the financial system themselves were having massive private gains at public loss. In this paper, it is addressed that how the crises happened and how ethics could have helped improving the vulnerability of the financial systems. This research paper will also include examples of the finance world gone bad, religious views and academic disciplines together with the laws and regulations which will be analyzed. With the collapse of the U.S. financial services industry, business ethics and corporate malpractices were often questioned by the media. One has to wonder what is the root of the problem? And what may be the solution? The core issue at the bank level was their approach to banking as they were caught up in an aggressive sales culture. Private banks have a strong culture of cross-selling their subsidiaries' products to increase the savings and current account deposits. Banks are generally being viewed solely as financial institutions which concern themselves with financial matters only and morality is seldom entered into the equation. This has allowed banks significant leeway in relation to ethical standards because they have not been associated with the actions undertaken by the businesses they lend to. But, with changing social demands and public awareness about the effects of banks’ lending policies, banks have begun to feel pressure from the society, NGOs and governments to go beyond their conventional business management. During a survey conducted by the Co-operative Bank of United Kingdom in the mid 1990s, the bank asked 6,000 customers on their thoughts on ethical banking and 84% responded positively. (Harvey,1995)The significance of this research is that we are living in a turbulence era and that the conventional banking system influenced by the theory of Adam Smith is collapsing. The author will attempt to answer the four research questions: the drivers, the challenges and success, current implementations and areas for improvement, and lastly the solutions to improve the banking system in Malaysia.